2016
DOI: 10.5664/jcsm.5676
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Item Instrument for Measuring Daytime Sleepiness: The Observation and Interview Based Diurnal Sleepiness Inventory (ODSI)

Abstract: The ODSI is a brief, valid, easy-to-administer three-item assessment that can screen for excessive daytime sleepiness among elderly patients with OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
1
25
0
1
Order By: Relevance
“…The first item scored from 0 to 12 helps to assess sleepiness or falling asleep in active situations or situations where a high level of stimulation is required (0 = not at all, 8 = mildly, 10 = moderately and 12 = very frequently). As falling asleep during active situations (the first item) is likely more dangerous, Onen et al 13 proposed to score it higher than following items. The second item scored from 0 to 6 helps to assess sleepiness during passive situations, such as while reading or watching TV (0 = not at all, 2 = mildly, 4 = moderately and 6 = very frequently).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first item scored from 0 to 12 helps to assess sleepiness or falling asleep in active situations or situations where a high level of stimulation is required (0 = not at all, 8 = mildly, 10 = moderately and 12 = very frequently). As falling asleep during active situations (the first item) is likely more dangerous, Onen et al 13 proposed to score it higher than following items. The second item scored from 0 to 6 helps to assess sleepiness during passive situations, such as while reading or watching TV (0 = not at all, 2 = mildly, 4 = moderately and 6 = very frequently).…”
Section: Methodsmentioning
confidence: 99%
“…The validation study of this questionnaire demonstrated that these items would ensure good coverage in the target population with high inter-rater agreement and test–retest reliability. 13 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations